Alginate films augmented with chlorhexidine hexametaphosphate particles provide sustained antimicrobial properties for application in wound care - Duckworth, Peter F.; Maddocks, Sarah E.; Rahatekar, Sameer S.; Barbour, Michele E. (Springer, 2020)
All chronic wounds are colonised by bacteria; for some, colonisation progresses to become infection. Alginate wound dressings are used for highly exuding chronic wounds as they are very absorbent, taking up large quantities of exudate while maintaining a moist wound bed to support healing. Some alginate dressings are doped with antimicrobials, most commonly silver, but evidence regarding the efficacy of these is largely inconclusive. This manuscript describes the development and in vitro assessment of alginate materials doped with chlorhexidine hexametaphosphate (CHX-HMP), a sparingly soluble salt which when exposed to aqueous environments provides sustained release of the common antiseptic chlorhexidine. Comparator materials were a commercial silver alginate dressing material and an alginate doped with chlorhexidine digluconate (CHXdg). CHX-HMP alginates provided a dose-dependent CHX release which was sustained for over 14 days, whereas CHXdg alginates released limited CHX and this ceased within 24 h. CHX-HMP and silver alginates were efficacious against 5 major wound pathogens (MRSA, E. coli, P. aeruginosa, K. pneumoniae, A. baumannii) in a total viable count (TVC) and an agar diffusion zone of inhibition (ZOI) model. At baseline the silver alginate was more effective than the CHX-HMP alginate in the TVC assay but the CHX-HMP alginate was the more effective in the ZOI assay. After 7 days’ artificial aging the CHX-HMP alginate was more effective than the silver alginate for four of the five bacteria tested in both assays. These materials may ultimately find application in the development of wound dressings for chronic wounds that provide sustained antimicrobial protection
Keywords: Alginate wound dressings